أحكام صلاة الصُّم والبُكم في الفقه الإسلامي - دراسة فقهية مقارنة - - سعدية, بوخشبة (University of Eloued جامعة الوادي, 2019)
"يتناول هذا البحث دراسة تتعلق بأحكام صلاة الصّم والبُكم في الفقه الإسلامي، والذي تمّ فيه جمع ما تناثر من آراء العلماء فيها ، وقد جاء معنونا بـ: ""أحكام صلاة الصُّم والبُكم في الفقه الإسلامي-دراسة فقهية مقارنة-""؛ وذلك في محاولة جادّة مني للإجابة على الإشكال الآتي: ما هي الأحكام الشرعية الخاصة بصلاة الصُّم والبُكم في الفقه الإسلامي ؟ وللإجابة على هذا السؤال فقد رسمت خطة كانت من مبحثين، حيث عُني المبحث الأوّل بالإطار النّظري للصّم والبُكم، بينما اختص المبحث الثّاني ببيان الجزء التطبيقي لبعض الأحكام المتعلِّقة بصلاة الصّم والبُكم في الفقه الإسلامي، هذا وقد توصَّلت الدراسة إلى نتائج عديدة أهمها: أن هذه الأحكام على حدِّ اطّلاعي، لم يفرد لها العلماء القدامى دراسة خاصة، بل أدرجوها في كتبهم ضمن أبواب العبادات، وبما أن فئة الصُّم والبُكم لا تنفك عن المجتمع، ونظرًا لأهمية الصّلاة، فإنَّ الأمر يستدعي من الفقهاء المختصّين إدراج أحكام صلاة هاته الفئة في كتاب خاص يسهُل الرّجوع إليه. " "This research is about the ""ahkam"" (judges) of the deaf and mutes 's prayers in the Islamic fikeh. In this research¸ opinions of scientists were gathered about this issue¸ and it was intiteled : "" Ahkam salat assom wa lbokm fi lfikh alislami - dirassa fikhia moukarina-"" My main goal was trying to Answer the following dilemma: What the specific religious Ahkam of the mutes and deaf 's prayers in the Islamic fikeh? So¸ to answer this question I designed a plan that contained two main branches The first one focused on the the theoretical frame of deafs and mutes ¸ while the second one was concerned with pointing out the applied part of some of the Ahkam that are related to mutes and deafs'prayers into the Islamic fikeh the study came to conclude multiple results such as: this issue _ AS FAR AS I KNOW_ was not given a personal study by the the ancient scientists but the included it into their books within the section of 'abwab al ibàda"" and since thé category of mutes and deaf is inseparable from the society¸ and regarding the huge importance of prayer... This issue demands that specialists in this field must include the ahkam of prayers of this category into aprivate book that it is easy to access. "
مذكرة ماستر تخصص فقه مقارن
Keywords: الصّم، البُكم، الصّلاة; deaf،mutes،prayer